(untitled) (Journal of Philosophy Culture and Political Science, 2020)
The article reveals the enduring value of the spiritual heritage of Abay and clarifies the value at the present time. Abay’s teaching, regardless of nationality, religion, races, is a worldwide spiritual teaching. Abay’s wisdom lies in his cognition of the world from a cognitive point of view. I would like to note that the works of Abay Kunanbayev vividly reflect the worldview, way of life, way of life, rituals and traditions of the Kazakh people. Emphasizing the value of the works and relying on the teachings of Abay, ways of overcoming the causes and consequences of the spiritual decline of humanity are proposed. Having shown the life philosophy of the Kazakh people through the worldview of Abay, the authors pay attention to the issues of the formation and education of an “integral personality” and emphasize the value of this idea in the modern period. The humanistic idea of Abay is comprehensively considered as the core of the life philosophy of the Kazakh people, the positive existential nature of Abay’s worldview, the problem of promoting Abay’s heritage, the role of Abay’s pragmatism in modern spiritual revival, the modern application of the categories of truthfulness and justice of Abay, the significance of Abay’s doctrine of honor and conscience in the modern world, the idea of a “good person”, views on education and science, Abay’s religious worldview. The article considers the Abai’s Heart as a center of deep meaning that connects the mind and conscience. The heart is recognized as the main form of conscious actions, such as thinking, reasoning,knowledge, and cognition. Connecting the world with the heart, which is created by rational vision, demonstrates the idea that the heart is the abode of humanity and virtue. The question of maintaining the heart in perfect purity is raised by considering the words of Edification of Abay. Key words: Abay, philosophy,” whole person”, kindness, personality, humanity, heart, mind.